The role of the gastric bacterial microbiome in gastric cancer: Helicobacter pylori and beyond. (December 2019) - Schulz, Christian; Schütte, Kerstin; Mayerle, Julia; Malfertheiner, Peter
A link between chronic inflammation and carcinogenesis has been depicted in many organ systems. Helicobacter pylori is the most prevalent bacterial pathogen, induces chronic gastritis and is associated with more than 90% of cases of gastric cancer (GC). However, the introduction of nucleotide sequencing techniques and the development of biocomputional tools have surpassed traditional culturing techniques and opened a wide field for studying the mucosal and luminal composition of the bacterial gastric microbiota beyond H. pylori . In studies applying animal models, a potential role in gastric carcinogenesis for additional bacteria besides H. pylori has been demonstrated. At different steps of gastric carcinogenesis, changes in bacterial communities occur. Whether these microbial changes are a driver of malignant disease or a consequence of the histologic progression along the precancerous cascade, is not clear at present. It is hypothesized that atrophy, as a consequence of chronic gastric inflammation, alters the gastric niche for commensals that might further urge the development of H. pylori -induced GC. Here, we review the current state of knowledge on gastric bacteria other than H. pylori and on their synergism with H. pylori in gastric carcinogenesis.